1988
DOI: 10.1007/bf00248756
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation of the human brain: responses in muscles supplied by cranial nerves

Abstract: The present investigation demonstrates that time-varying magnetic fields induced over the skull elicit distinct types of responses in muscles supplied by the cranial nerves both on the ipsilateral and the contralateral side. When the center of the copper coil was positioned 4 cm lateral to the vertex on a line from the vertex to the external auditory meatus, bilateral responses in the masseter, orbicularis oculi, mentalis, and sternocleidomastoideus muscles with a delay of about 10 to 14 ms after the stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
0
8

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(77 citation statements)
references
References 22 publications
12
57
0
8
Order By: Relevance
“…This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…Again, the evidence comes from stroke patients in whom bilateral voluntary movements can be made with upper but not lower part of the face. Benecke et al (1988b) found that they could obtain ipsilateral responses after magnetic stimulation of the motor cortex in mentalis and masseter muscles with a latency of between 10 and 15 ms. This was longer than the latency from direct excitation of the facial or trigeminal nerves (about 3-4 ms) and, because it was approximately the same as the latency from stimulation of the contralateral cortex, it was presumed to be due to a projection from the ipsilateral motor cortex.…”
Section: Interruption Of Brain Activity By Cortical Stimulationmentioning
confidence: 99%
“…For facial nerve innervated muscles, the central conduction time is longer. Benecke, Meyer, Schonle & Conrad (1988b) and Cohen & Hallett (1988) Gandevia & Rothwell (1987) and Hess et al (1987a) showed that the first motor unit recruited by both electrical and magnetic stimulation was the same as that recruited in a voluntary contraction. Thus, it is tempting to suggest that cortical stimulation also recruits units according to the size principle.…”
Section: Calculation Of Central Motor Conduction Timementioning
confidence: 99%
“…A privação dos movimentos faciais limita, de forma dramática, a integração do ser humano com seu próximo alguns músculos da porção inferior, e não todos, o que poderia explicar a persistência funcional de alguns grupos musculares frente a lesões que deveriam provocar déficits completos 1,5,10 . O núcleo facial recebe informações dos dois hemisférios e está localizado na região lateral da porção inferior da ponte.…”
Section: Revisão De Literaturaunclassified
“…As informações geradas pelo córtex motor trafegam pelo tronco cerebral através do trato corticobulbar, juntamente com o trato corticoespinal (ou piramidal), passando pelo joelho da cápsula interna (Figura 2). Ao chegar à porção média da ponte, as fibras do trato corticonuclear se separam do trato corticoespinal e se direcionam ao núcleo facial 1,4,11,12 . Há vários anos prevalecia o conceito de que as fibras responsáveis pela inervação dos músculos da porção inferior da face (orbicular da boca, bucinador e platisma) seriam cruzadas, isto é, viriam apenas do hemisfério contralateral, enquanto as fibras destinadas aos músculos da porção superior da face (músculo frontal, corrugador do supercílio, orbicular do olhos) seriam provenientes tanto do hemisfério ipsi como do hemisfério contralateral.…”
unclassified